Influence of the COVID-19 Pandemic on the Treatment Patterns and Outcomes of Colorectal Cancer - In Ja Park (The Ewha Medical Journal)
Over the past 3 years, the COVID-19 pandemic has posed significant challenges to the healthcare system, leading to delays in the diagnosis and treatment of various diseases due to the need for social distancing measures. Colorectal cancer has not been immune to these disruptions, and research in various countries has explored the impact of COVID-19 on the diagnosis and treatment of colorectal cancer. One notable consequence has been the postponement of colorectal cancer screenings, potentially resulting in disease progression, which can adversely affect surgical and oncological outcomes. Furthermore, the treatment approach for colorectal cancer may vary depending on the extent of disease progression and the healthcare policies implemented in response to the COVID-19 pandemic. In this systematic review, we examine treatment strategies, surgical outcomes, and oncological variables across multiple studies focusing on colorectal cancer treatment during the COVID-19 pandemic. The purpose of this analysis was to assess how medical policies enacted in response to the COVID-19 pandemic have influenced the outcomes of colorectal cancer treatment. We hope that this review will provide valuable insights and serve as a foundational resource for developing guidelines to address potential medical crises in the future.